Examining the Paradigmatic Shift in Legal Policies Concerning Land Redistribution as an Imperative Obligation Imposed on Plantation Companies for the Advancement of Community Plantation Enterprises - Tarbarita Simorangkir; Ellydar Chaidir; Thamrin S (Rechtsnormen: Journal of Law, 2024)
Background. The existence of Article 28 of Law Number 11 of 2020 in conjunction with Government Regulation in Lieu of Law Number 2 of 2022 and Law Number 6 of 2023 Paragraph 3 on Job Creation, Government Regulation Number 26 of 2021 on the Implementation of the Agricultural Sector. Purpose. Minister of Agriculture Regulation Number 18 of 2021 on the Facilitation of Community Plantation Development, Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Regulation Number 18 of 2021 on the Procedures for Determining Management Rights and Land Rights, and Circular Letter of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 11/Se-Hk.02.02/Viii/2020. Method. the Implementation of Company Obligations in Facilitating Community Plantation Development collectively render the imperative of land redistribution for community plantations, constituting 20% of the aggregate land entitlements vested in plantation enterprises, not as an enforceable obligation but rather as an elective premise, wherein the ethos of facilitating community plantation development is underscored. This scholarly inquiry adopts a Normative Juridical methodology, employing both legislative scrutiny and a case study approach. Results. The findings assert, that the extant regulatory framework concerning land redistribution, as a commitment levied upon plantation entities for fostering community plantation initiatives, presently lacks parity, given that the apportionment of 20% (twenty percent) of land expanses granted under Business Use Rights or from the territories delineated in Plantation Conclusion. Business Licenses or Cultivation Business Licenses, earmarked for community beneficiaries, no longer carries the hallmark of an obligatory tenet but is relegated to the sphere of discretionary choice within the ambit of community plantation development facilitation programs.